2006
DOI: 10.1017/s0022029906002172
|View full text |Cite
|
Sign up to set email alerts
|

Associations between somatic cell counts at calving or prior to drying-off and clinical mastitis in the remaining or subsequent lactation

Abstract: Data from 350 herds enrolled in the Norwegian Dairy Herd Recording System (NDHRS) were used to investigate the associations between the first two cow-milk somatic cell counts (SCC) test-days' results after calving or the three last SCC test-days prior to drying off in the first lactation and the hazard ratio (HR) of clinical mastitis (CM) during the remaining first or the subsequent second lactation respectively. Altogether, 9519 first lactations and 6046 second lactations were included. Cox regression analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
0
24
0
2
Order By: Relevance
“…To further increase production in an ecologically and economically responsible manner, investing in optimal udder health and robust cattle is necessary. For dairy cows, the dry period is an important period for udder health because dry cows can cure from IMI present at dry-off (Bradley and Green, 2000;Dingwell et al, 2004) but udder health can also be threatened as many cows acquire new IMI in the dry period Green, 2000, 2001;Whist and Østeras, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To further increase production in an ecologically and economically responsible manner, investing in optimal udder health and robust cattle is necessary. For dairy cows, the dry period is an important period for udder health because dry cows can cure from IMI present at dry-off (Bradley and Green, 2000;Dingwell et al, 2004) but udder health can also be threatened as many cows acquire new IMI in the dry period Green, 2000, 2001;Whist and Østeras, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Care must be taken in interpreting the results of experimental studies such as these, however, as the first line of defense (the teat end) is often bypassed by infusion of challenge organisms, making it difficult to compare them to the observational literature. Other studies have shown increased risk of clinical mastitis as SCC rises (Dohoo et al, 1984;Beaudeau et al, 1998;Whist and Østerås, 2007). As bacteriological culturing was not done on these quarters and clinical mastitis was used as the outcome, these papers are presumably documenting the increased probability that cows with subclinical IMI are more likely to develop clinical mastitis.…”
Section: Sccmentioning
confidence: 98%
“…In experiments and field trials, selection for treatment was mostly based on SCC and bacteriological culture samples to diagnose IMI (Østerås et al, 1994;Whist and Østerås, 2007). In the Netherlands, farmers generally tend to select cows on the basis of the SCC values of the last 3 test-days and/or the clinical IMI history of the cow.…”
Section: Discussionmentioning
confidence: 99%